Renal Implications of Psoriasis: Urinary Podocyte Markers and Disease Progression - Gencoglu, Sule; Yardim, Meltem; Akkoc, Ramazan Fazil (Mattioli 1885, 2025)
Introduction: Psoriasis may lead to glomerular inflammatory damage and disruption of the podocyte barrier, allowing podocyte degradation products to leak into the urine. Objectives: We aimed to analyze the concentrations of podocyte surface glycoprotein podocalyxin (PDX) and podocyte slit protein nephrin in spot urine samples from patients with mild, moderate, or severe psoriasis vulgaris. Methods: A total of 78 participants, including 58 patients diagnosed with mild, moderate, or severe psoriasis vulgaris and 20 healthy controls, were included in the study. Psoriasis was diagnosed based on the typical morphological characteristics of the lesions. Morning urine samples were used to evaluate urine PDX and nephrin levels. Albuminuria was evaluated by calculating the urine albumin-tocreatinine ratio (uACR). Results: Urinary PDX and nephrin levels were significantly higher in the psoriasis group than in the control group. Urinary PDX and nephrin levels in the mild and moderate psoriasis groups were similar but higher than those in the control group and significantly higher in the severe psoriasis group than in the mild and moderate psoriasis groups. The microalbuminuria rates were similar between the psoriasis and control groups. A significant positive correlation was observed between urine PDX, nephrin, uACR, and SBP. After adjusting for age, BMI, and sex, urine PDX and nephrin levels were found to be independent risk factors for microalbuminuria. Conclusion: This study showed that podocyte damage in patients with psoriasis begins in the early stages of the disease and significantly increases in the severe stage of the disease.
Keywords: Psoriasis vulgaris; Podocytes; Podocalyxin; Nephrin; Albuminuria